(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
Heavy metal contamination of agricultural soils, particularly with lead (Pb), has emerged as a pressing environmental concern due to its detrimental effects on crop development, soil fertility, and public health. Lead is a non-essential and highly toxic metal that can accumulate in plant tissues, disrupt physiological processes, and enter the food chain, thereby compromising food quality and safety. This study aimed to assess the impact of different Pb concentrations on the growth performance and physiological characteristics of Lactuca sativa (lettuce), a widely consumed leafy vegetable known for its sensitivity to soil pollutants. The experiment was conducted under controlled greenhouse conditions at the Institute for Agricultural Research, Zaria. Uniform seeds of L. sativa were planted in 15 pots filled with standardized loamy soil, and five treatment levels of lead were applied using lead nitrate [Pb(NO₃)₂] at concentrations corresponding to 0 g (control), 500 g, 1000 g, 1500 g, 2000 g, and 2500 g per pot. The plants were monitored for a period of eight weeks, during which key growth parameters were measured, including plant height, leaf number, canopy diameter, vegetative vigor, and chlorophyll content (measured via SPAD meter). Results revealed that increasing Pb concentrations had a statistically significant negative impact on all measured growth indices. Moderate Pb levels (500–1000 g) induced slight reductions in growth, possibly due to the plant’s short-term adaptive responses such as antioxidant defense or osmotic adjustment. However, at higher concentrations (1500–2500 g), a sharp decline in plant height, leaf development, chlorophyll content, and canopy spread was observed, indicating systemic toxicity and impaired physiological functions. Chlorosis, stunted growth, and leaf deformation were also more pronounced at elevated Pb levels. The data suggest a nonlinear dose response relationship between Pb exposure and plant growth, with evidence of limited tolerance at low to-moderate contamination but severe suppression at higher levels. The reduction in chlorophyll content points to Pb-induced interference in photosynthesis, while decreased vegetative vigor and canopy size reflect inhibited cell division and elongation. This study highlights the susceptibility of Lactuca sativa to lead toxicity and the potential health risks associated with growing edible crops in contaminated soils. The findings emphasize the critical need for environmental monitoring, safe agricultural practices, and the implementation of soil remediation strategies such as phytoremediation, soil washing, or amendment with organic matter to mitigate heavy metal accumulation in food crops. Ultimately, ensuring soil health is imperative for safeguarding food quality, human health, and sustainable agricultural development.